2012
DOI: 10.1016/j.profnurs.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Knowledge Gains Using Simulation in the Education of Prelicensure Nursing Students

Abstract: Gains in knowledge and self-efficacy using human patient simulation (HPS) in the education of prelicensure nursing students have been reported. However, the predictors of improved learning outcomes using this teaching methodology are not known. Using a two-group (participated in HPS, did not participate in HPS), repeated-measures, experimental design, we examined the predictors of higher scores on a Knowledge Questionnaire in 162 students (age = 25.7 ± 6.6, gender = 85.5% female) from four prelicensure cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 15 publications
2
29
2
Order By: Relevance
“…Results of this study are congruent with the findings of others such that prelicensure nursing students gain confidence (SE) and knowledge with an HPS experience (Alinier et al, 2006;Brannan et al, 2008;Jeffries & Rizzolo, 2006;Kardong-Edgren et al, 2009;Linden, 2008;Ravert, 2004;Shinnick et al, 2011;Shinnick & Woo, 2012). However, a significant correlation between SE and knowledge was not found.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of this study are congruent with the findings of others such that prelicensure nursing students gain confidence (SE) and knowledge with an HPS experience (Alinier et al, 2006;Brannan et al, 2008;Jeffries & Rizzolo, 2006;Kardong-Edgren et al, 2009;Linden, 2008;Ravert, 2004;Shinnick et al, 2011;Shinnick & Woo, 2012). However, a significant correlation between SE and knowledge was not found.…”
Section: Discussionsupporting
confidence: 88%
“…Although some investigators have reported knowledge gains using HPS (Alinier, Hunt, Gordon, & Colin, 2006;Brannan, White, & Bezanson, 2008;Jeffries & Rizzolo, 2006;Kardong-Edgren, Lundstrom, & Bendel, 2009;Linden, 2008;Ravert, 2004;Shinnick, Woo, Horwich, & Steadman, 2011;Shinnick & Woo, 2012), there continues to be a preponderance of published studies touting the benefits of HPS based solely on gains in student confidence or SE (Bearnson & Wiker, 2005;Bremner, Aduddell, Bennett, & VanGeest, 2006;Brown & Chronister, 2009;Feingold, Calaluce, & Kallen, 2004;Gordon & Buckley, 2009;Jarzemsky & McGrath, 2008;Kameg et al, 2010;Leigh, 2008a;Nishisaki, Keren, & Nadharni, 2007;Pike & O'Donnell, 2010;Reznek et al, 2003;Sherman, 2002;Smith, 2008;Taekman, Hobbs, & Wright, 2007;Tuttle, 2009). However, the relationships between SE and knowledge and HPS are unclear.…”
Section: Hps and Knowledgementioning
confidence: 99%
“…There is evidence that using this method is more effective for the acquisition of knowledge than using only case studies or other strategies (9)(10) . In clinical practice, simulations promote changes in attitudes and a significant reduction of adverse events, thus, contributing to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in keeping with other international simulation nursing studies that find that high-fidelity simulation enhances scores on both knowledge and skills exams [43] and leads to higher knowledge scores. [44] Cant and Cooper [38] described twelve studies that used an experimental or quasi-experimental design, all of which all found simulation to be a valid teaching/learning strategy; gains in knowledge, critical thinking, ability, satisfaction and competence were also seen in half of these studies. Still, Kaplan, Abraham and Gary [45] found in their study no significant differences between active participation and mere observation during simulation in regard to test scores.…”
Section: Discussionmentioning
confidence: 99%